Classification of factors influencing environmental management of enterprise - Tambovceva, Tatjana (Technological and Economic Development of Economy, 2016)
The modern enterprises consider the sustainable development as the one of basic conceptions of one’s activity. In recent years, an increasing number of private as well as public organizations have been engaged with implementation and using of environmental management systems (EMSs). The research is built up by two main parts. In the first, author prepared theoretical analyses of literature and scientific publications. The second part based on survey results collected from Latvian companies using in depth interviews. Author proposes that the process of environmentally oriented business should be studied as a multi-dimensional issue. Company’s external and internal environment elements were shown. In article author also investigated different factors influencing company’s environmental management and motives of implementing EMS.First published online: 29 Jun 2016